2013
DOI: 10.1007/jhep11(2013)027
|View full text |Cite
|
Sign up to set email alerts
|

Striped phases in the holographic insulator/superconductor transition

Abstract: We study striped phases in holographic insulator/superconductor transition by considering a spatially modulated chemical potential in AdS soliton background. Generally striped phases can develop above a critical chemical potential. When the constant leading term in the chemical potential is set to zero, a discontinuity in the plot of charge density versus chemical potential is observed in the limit of large wave vector. We explain this discontinuity using an analytical approach. When the constant leading term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 103 publications
0
36
0
1
Order By: Relevance
“…5 Holographic superconductors with spatially modulated orders have been studied in a number of setups, starting with [19], in which striped modulations were sourced by a periodic chemical potential, with many generalizations in the literature since then, e.g. [20][21][22][23][24]. A study of backreaction by adding a lattice in the form of a periodic potential was reported in [25].…”
Section: Jhep08(2017)081mentioning
confidence: 99%
“…5 Holographic superconductors with spatially modulated orders have been studied in a number of setups, starting with [19], in which striped modulations were sourced by a periodic chemical potential, with many generalizations in the literature since then, e.g. [20][21][22][23][24]. A study of backreaction by adding a lattice in the form of a periodic potential was reported in [25].…”
Section: Jhep08(2017)081mentioning
confidence: 99%
“…Interplay of disorder effect and periodic effect.-Holographic superconductor with periodic chemical potential has been studied in [25][26][27]. In [26,27] the authors found that the superconductivity is enhanced by the presence of the periodic chemical potential.…”
mentioning
confidence: 99%
“…In [26,27] the authors found that the superconductivity is enhanced by the presence of the periodic chemical potential. In Fig.…”
mentioning
confidence: 99%
“…We would like to extend the discussion of the inhomogeneity to the AdS soliton background. First attempt in this direction was reported in [16]. We will show more behaviors of the strongly coupled striped insulator and its dependence on the inhomogeneity.…”
Section: Introductionmentioning
confidence: 81%
“…This is very different from the behavior of the conductivity perpendicular to the direction of the stripe. In [16] it was noticed that the conductivity perpendicular to the direction of the stripe is not much modified by the the spacial modulation, because as ω → 0 the conductivity becomes a delta function for various spacial modes. We hope to present the numerical result for the conductivity along the direction of stripe in the future.…”
Section: Striped Phases In the Holographic Insulatormentioning
confidence: 99%